Formulation of the Concept of Legal Capacity to Conduct Marriages for Persons with Autism Spectrum Disorder - Yuli Kristina; Saifullah; Burhanuddin Susamto (Faculty of Law, Universitas Pekalongan, 2025)
This study explores the formulation of legal capacity for individuals with Autism Spectrum Disorder (ASD) to enter into marriage within the Indonesian legal system. Marriage, as both a civil act and a human right, requires the capacity to fulfill rights and obligations, yet current regulations provide limited guidance for individuals with developmental disabilities. Although the Marriage and the Disability Law recognize the right of persons with disabilities to marry, the absence of explicit provisions on ASD raises challenges in legal practice. The research adopts an empirical juridical and qualitative approach, utilizing interviews with judges, psychologists, parents, and individuals with autism, supported by statutory analysis. Findings indicate that individuals with mild autism or Asperger’s syndrome may retain sufficient mental competence to exercise legal rights, although their capacity can vary. The study applies two theoretical frameworks: maqashid sharia which emphasizes the protection of religion, life, intellect, lineage, and property and the theory of legal certainty, highlighting justice, benefit, and consistency in legal rules. Together, these approaches advocate for an inclusive and rights-based interpretation of marriage law. The research underscores the need for a legal construction that accommodates ASD by integrating medical, psychological, and jurisprudential assessments. Judicial reasoning should move beyond rigid textual interpretations to purposive approaches that balance individual rights with public interest. Ultimately, the study proposes that ASD be recognized under the category of “developmental disabilities” within the Disability Law, ensuring a fair, clear, and implementable standard of legal competence for marriage. This framework aspires to advance inclusive family law that upholds dignity, equality, and social justice.